393 What Are the Risk Factors for Anastomotic Stricture After Bile Duct Injury Repair? A Systematic Review and Meta-Analysis. (4th May 2021) - Hall, L; Halle-Smith, J; Hodson, J; Roberts, K
Abstract: Introduction: Hepaticojejunostomy (HJ) is the standard repair following major bile duct injury (BDI), but anastomotic stricture can result in long-term morbidity. There is a need to assimilate high-level evidence to establish risk factors for the development of anastomotic stricture after HJ for BDI. Method: A systematic review of studies reporting the rate of anastomotic stricture after HJ for BDI was performed according to PRISMA guidelines. Meta-analyses of proposed risk factors were then performed. Results: Meta-analysis included five factors (n = 2, 198 patients, 17 studies). Vascular injury (OR 2.71; 95%CI 1.37-5.35; p = 0.004), postoperative bile leak (OR: 8.03; 95%CI 2.04-31.71; p = 0.003), previous repair (OR: 5.36; 95%CI 1.04-27.76;p=0.05) and repair by non-specialist surgeon (OR 11.29; 95%CI 5.21-24.47; p < 0.0001) were associated with HJ stricture after BDI. Strasberg injury grade was not associated with HJ stricture (OR: 1.05; 95%CI 0.63-1.75; p = 0.86). Due to heterogeneity of reporting it was not possible to perform meta-analysis for impact of timing of repair on anastomotic stricture rate. Conclusions: This meta-analysis identifies factors that significantly increase the rate of anastomotic stricture after HJ for BDI. Knowledge of these risk factors will allow risk stratification in terms of follow-up for individual cases, better informed consent, and guidance for medico-legal cases.